Replication of an Experimental Study Investigating the Efficacy of a Multisyllabic Word Reading Intervention With and Without Motivational Beliefs Training for Struggling Readers. (January 2019) - Toste, Jessica R.; Capin, Philip; Williams, Kelly J.; Cho, Eunsoo; Vaughn, Sharon
This randomized control trial examined the efficacy of an intervention aimed at improving multisyllabic word reading (MWR) skills among fourth- and fifth-grade struggling readers ( n = 109, 48.6% male), as well as the relative effects of an embedded motivational beliefs training component. This study was a closely aligned replication of our earlier work. The intervention was replicated with a three-condition design: MWR only, MWR with a motivational beliefs component, and business-as-usual control. Students were tutored in small groups for 40 lessons (four 40-min lessons each week). When we combined performance of students in both MWR conditions, intervention students significantly outperformed controls on proximal measures of affix reading and MWR, as well as standardized measures of decoding, spelling, and text comprehension. Furthermore, there was a noted interaction between English learner status and treatment on spelling performance. There were no statistically significant main effects between the MWR groups on proximal or standardized measures of interest. Findings are discussed in terms of their relevance to MWR instruction for students with persistent reading difficulties and considerations for future research related to the malleability of motivation.